Efficiency of nitrogen fertilization associated with urease inhibitor in irrigated mexican sunflower cultivation (Research, Society and Development, 2021)
The use of urea as a fertilizer implies high N-NH3 losses. These losses compromise the sustainability of nitrogen fertilization in intensive forage production systems, even in irrigated areas in tropical regions. Thus, it is essential to adopt management practices that favor the efficiency of the use of N-urea by plants. Therefore, it was evaluated the application of urea doses associated or not with the urease inhibitor NBPT® on soil NH3-N losses by volatilization, productivity, and N use efficiency in Tithonia diversifolia in irrigated cultivation. A randomized block design was used, with four replications, in a 2 x 5 factorial scheme, the first factor being urea associated or not with the urease inhibitor NBPT®, and the second represented by doses of 0, 50, 100, 150 and 200 kg ha-1 of N. The greatest losses of N-NH3 in the soil were observed on the 6th day after application, in treatments without urease inhibitor and in the highest doses of urea. The use of NBPT® reduced the loss of N-NH3 in the soil to less than 5% of the applied doses. NBPT® mixed with urea increases the agronomic efficiency of N use and productivity by T. diversifolia compared to the use of fertilizer without this inhibitor. The efficiency of the use of the applied nutrient has an inverse behavior to the increase of the applied N dose, being the best cost-benefit referring to the forage productivity (12,000 kg ha-1 of dry mass) obtained with the application of 50 kg ha-1 of N with NBPT®.